Safety evaluation of TOPAZ-1 and KEYNOTE-966 regimens in metastatic biliary tract cancer: a systematic review and meta-analysis - Elsa Vitale; Lorenza Maistrello; Francesco Ciccimarra; Deniz Can Guven; Taha Koray Sahin; Fernando Sabino Marques Monteiro; Raffaele de Luca; Matteo Scaramuzzi; Sabina Delcuratolo; Oronzo Brunetti; Alessandro Rizzo; Giovanni Brandi (Clinical & Experimental Metastasis, 2026)

Hyponatremia in cancer patients receiving immune checkpoint inhibitors: the ARON-MOUSEION-014 meta-analysis - Elsa Vitale; Lorenza Maistrello; Francesco Ciccimarra; Alessandro Rizzo; Andrey Soares; Oronzo Brunetti; Veronica Mollica; Brigida Anna Maiorano; Mauro Francesco Pio Maiorano; Fernando Sabino Marques Monteiro; Francesco Massari; Matteo Santoni (Cancer and Metastasis Reviews, 2026)

Soil CO2 emissions during the winter–summer crop rotation fallow period: Influence of tillage, nitrogen fertilization, and weed growth in a long-term field trial - Matteo Francioni; Paride D’Ottavio; Marco Bianchini; Paola Antonia Deligios; Luigi Ledda; Chiara Rivosecchi; Federico Mammarella; Alessio Giampieri; Gianluca Brunetti; Stefano Zenobi; Marco Fiorentini; Biagio Di Tella; et al. (Agriculture, Ecosystems & Environment, 2025)

Mediterranean pine forests: Comparison of fluxes and tree rings of Pinus pinaster Aiton and Pinus pinea L - Nicola Arriga; Matteo Campioli; Mara Bernardi; Andrea Cerasa; Josep Peñuelas; Michele Brunetti; Claudia Cocozza; Alessandro Dell’Acqua; Ernest N. Koffi; Ignacio Goded; Giovanni Manca; Marco Matteucci; et al. (Agricultural and Forest Meteorology, 2025)

Prognostic immunotherapy score (PIS) in patients with advanced urothelial carcinoma treated with pembrolizumab: real-world data and validation from ARON-2 dataset - Alessandro Rizzo; Anas Zayed; Elsa Vitale; Sebastiano Buti; Hideki Takeshita; Simon Crabb; Giandomenico Roviello; Emmanuel Seront; Jose Carlos Tapia; Sarah Scagliarini; Lazar Popovic; Ray Manneh Kopp; et al. (Clinical & Experimental Metastasis, 2025)

Metastatic sites and clinical outcomes in renal cell carcinoma patients receiving immune-based combinations: the MOUSEION-08 study - Alessandro Rizzo; Fernando Sabino Marques Monteiro; Veronica Mollica; Oronzo Brunetti; Elsa Vitale; Angela Monica Sciacovelli; Andrey Soares; Francesco Massari; Matteo Santoni (Clinical & Experimental Metastasis, 2025)

Impact of time-of-day administration of immunotherapy on survival in metastatic renal cell carcinoma: the MOUSEION-09 meta-analysis - Alessandro Rizzo; Fernando Sabino Marques Monteiro; Veronica Mollica; Andrey Soares; Oronzo Brunetti; Angela Dalia Ricci; Francesco Massari; Matteo Santoni (Clinical & Experimental Metastasis, 2025)

Multi-scale assessment of high-resolution reanalysis precipitation fields over Italy - Francesco Cavalleri; Cristian Lussana; Francesca Viterbo; Michele Brunetti; Riccardo Bonanno; Veronica Manara; Matteo Lacavalla; Simone Sperati; Mario Raffa; Valerio Capecchi; Davide Cesari; Antonio Giordani; et al. (Atmospheric Research, 2024)

Inter‐comparison and validation of high‐resolution surface air temperature reanalysis fields over Italy - Francesco Cavalleri; Francesca Viterbo; Michele Brunetti; Riccardo Bonanno; Veronica Manara; Cristian Lussana; Matteo Lacavalla; Maurizio Maugeri (International Journal of Climatology, 2024)
Surface air temperature (t2m) data are essential for understanding climate dynamics and assessing the impacts of climate change. Reanalysis products, which combine observations with retrospective short‐range weather forecasts, can provide consistent and comprehensive datasets. ERA5 represents the state‐of‐the‐art in global reanalyses and supplies initial and boundary conditions for higher‐resolution regional reanalyses designed to capture finer‐scale atmospheric processes. However, these products require validation, especially in complex terrains like Italy. This study analyses the capability of different reanalysis products to reproduce t2m fields over Italy during the 1991–2020 period. The analyses encompass ERA5, ERA5‐Land, the MEteorological Reanalysis Italian DAtaset (MERIDA), the Copernicus European Regional ReAnalysis (CERRA), and the Very High‐Resolution dynamical downscaling of ERA5 REAnalysis over ITaly (VHR‐REA_IT). The validation we conduct pertains to both the spatial distribution of 30‐year seasonal and annual normal values and the daily anomaly records. Each reanalysis is compared with observations projected onto its respective grid positions and elevations, overcoming any model bias resulting from an inaccurate representation of the real topography. Key findings reveal that normal values in reanalyses closely match observational values, with deviations typically below 1°C. However, in the Alps, winter cold biases sometimes exceed 3°C and show a relation with the elevation. Similar deviations occur in the Apennines, Sicily, and Sardinia. Conversely, VHR‐REA_IT shows a warm bias in the Po Valley up to 3°C in summer. Daily anomalies generally exhibit lower errors, with MERIDA showing the highest accuracy and correlation with observational fields. Moreover, when aggregating daily anomalies to annual time scales, the errors in the anomaly records rapidly decrease to

Soil invertebrate biodiversity and functionality within the intensively farmed areas of the Po Valley - Matteo Brunetti; Giulia Magoga; Alex Cussigh; Sumer Alali; Flavia Pizzi; Paola Cremonesi; Ilaria Di Lelio; Andrea Becchimanzi; Roberto Comolli; Pietro Marino Gallina; Gustavo Gandini; Alberto Spada; et al. (Applied Soil Ecology, 2024)

Biotic and abiotic factors affecting the microbiota of Chrysomelidae inhabiting wetland vegetation - Giulia Magoga; Matteo Brunetti; Lukasz Kajtoch; Alberto Spada; Matteo Montagna (Hydrobiologia, 2023)
A subject of particular interest concerns the understanding of which biotic and/or abiotic factors shape the insect’s microbiota composition and diversity. In this study, we focus our attention on the microbiota associated with leaf beetles (Coleoptera: Chrysomelidae) inhabiting a freshwater wetland in Northern Italy for investigating which factors shape it in this peculiar environment. A DNA metabarcoding approach targeting the 16S rRNA has been used to characterize the bacteria associated with seven leaf beetles species living in different zones of the wetland (trees/shrubs, meadow and emergent vegetation zones). The obtained results suggest that three factors potentially affecting microbiota diversity and composition are species membership in the first place, then living zone in the wetland and sex. Within the studied species, males were found possibly more prone to acquire bacteria from the surrounding environment, while females’ microbiota of most of the species resulted dominated by symbiotic bacteria (reproductive manipulators, e.g. Wolbachia , or other symbionts with functional roles in the species, e.g. Candidatus Macropleicola in Donacia genus). The present study, even if based on a limited sample size, contributed to exploring the factors affecting the composition and diversity of bacteria associated with Chrysomelidae.

Does diet breadth affect the complexity of the phytophagous insect microbiota? The case study of Chrysomelidae - Matteo Brunetti; Giulia Magoga; Fabrizia Gionechetti; Alessio De Biase; Matteo Montagna (Environmental Microbiology, 2022)
Summary Chrysomelidae is a family of phytophagous insects with a highly variable degree of trophic specialization. The aim of this study is to test whether species feeding on different plants (generalists) harbour more complex microbiotas than those feeding on a few or a single plant species (specialists). The microbiota of representative leaf beetle species was characterized with a metabarcoding approach targeting V1–V2 and V4 regions of the bacterial 16S rRNA. Almost all the analysed species harbour at least one reproductive manipulator bacteria (e.g., Wolbachia , Rickettsia ). Two putative primary symbionts, previously isolated only from a single species ( Bromius obscurus ), have been detected in two species of the same subfamily, suggesting a widespread symbiosis in Eumolpinae. Surprisingly, the well‐known aphid symbiont Buchnera is well represented in the microbiota of Orsodacne humeralis . Moreover, in this study, using Hill numbers to dissect the components of the microbiota diversity (abundant and rare bacteria), it has been demonstrated that generalist insect species harbour a more diversified microbiota than specialists. The higher microbiota diversity associated with a wider host‐plant spectrum could be seen as an adaptive trait, conferring new metabolic potential useful to expand the diet breath, or as a result of environmental stochastic acquisition conveyed by diet.

Effect of SAcubitril/Valsartan on left vEntricular ejection fraction and on the potential indication for Implantable Cardioverter Defibrillator in primary prevention: the SAVE-ICD study - Federico Guerra; Ernesto Ammendola; Matteo Ziacchi; Vittorio Aspromonte; Pier Luigi Pellegrino; Giuseppe Del Giorno; Gabriele Dell’Era; Lorenzo Pimpini; Francesco Santoro; Roberto Floris; Giulia Stronati; Gerardo Nigro; et al. (European Journal of Clinical Pharmacology, 2021)

Underwater Noise Monitoring with Real-Time and Low-Cost Systems, (The CORMA Experience) - Paolo Diviacco; Antonio Nadali; Massimiliano Iurcev; Mihai Burca; Rodrigo Carbajales; Matteo Gangale; Alessandro Busato; Fabio Brunetti; Lorenzo Grio; Alberto Viola; Nikolas Potleca (Journal of Marine Science and Engineering, 2021)
Marine life can be severely affected by anthropogenic underwater noise. This latter increased proportionally to the rise of human activities such as maritime traffic, marine civil engineering works, oil- and gas-related activities or offshore wind farms; so much so that, currently, it can be considered a threat to the environment. Assessing underwater noise requires quite some investments both in personnel and instrumentation. If this is affordable by several governmental and scientific organizations, this cannot be extended straightforwardly to all research initiatives or to developing countries. In addition, time and geographic coverage of monitoring can also be significantly limited by the costs of multiple installations. We explore the possibility to use a solution based on off-the-shelf and low-cost technologies combined with a scalable infrastructure developed with open-source tools only. The perspective to avoid proprietary solutions allows great flexibility in extending the current paradigm toward real-time transmission, processing, and web-based data access. Our solution has been deployed at sea in November 2020 and is providing data continuously ever since. First results from the analysis of these data allowed us to highlight several interesting abiotic and anthropogenic temporal patterns.

Class inclusion versus quantifiers comprehension tasks: an experimental study with school-aged children - Marcella Brunetti; Rosalia Di Matteo; Tiziana Aureli; Maria Concetta Garito; Claudia Casadio (Cognitive Processing, 2021)

Diagnosing acute encephalitis in patients with hematological disorders: caveats and pitfalls - Elisa Vegezzi; Giulia Berzero; Desiree Barbetta; Anna Amelia Colombo; Oscar Borsani; Paolo Bernasconi; Francesca Compagno; Marco Zecca; Giulia Campanini; Anna Simoncelli; Matteo Paoletti; Anna Pichiecchio; et al. (Journal of NeuroVirology, 2020)